Pengaruh Struktur Aset, Likuiditas dan Profitabilitas Terhadap Struktur Modal Pada Perusahaan Subsektor Perdagangan Besar Yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015 - Thomas firdaus Hutahaean; Dewita Purba (Journal of Business and Economics Research (JBE), 2020)
The approach uses a quantitative approach, descriptive research methods, the nature of causal research and multiple linear regression analysis methods. The results showed that the asset structure, liquidity and profitability had a simultaneous effect on the capital structure of the Large Trade Subsector Company listed on the Indonesia Stock Exchange for the 2012-2015 period with a value of Fcount> Ftable or 11,596> 2.78 with a significance level of 0,000. Partially the asset structure does not have a positive and insignificant effect on capital structure, partially liquidity has a negative and significant effect on capital structure, and partially profitability has a negative and significant effect on capital structure. The test results of the coefficient of determination showed that 36.6% of the variation in asset structure, liquidity and profitability variables explained the relationship of variation to capital structure variables in the large trading subsector companies listed on the Indonesia Stock Exchange for the period 2012-2015.